30 years of samples submitted to an Australian Medical Entomology Department. Issue 1 (13th July 2020) - Geary, Merilyn J; Russell, Richard C; Moerkerken, Leendert; Hassan, Assareh; Doggett, Stephen L
Abstract: Arthropods are the cause of considerable human morbidity. In spite of numerous text books and reviews published on arthropods of medical importance, this is the first paper in the world to present a comprehensive review of specimens sent to a medical entomology laboratory over an extended period. The Department of Medical Entomology at Westmead Hospital is the New South Wales reference laboratory for arthropods of medical importance. In the years 1988–2017, there were 5655 samples submitted for identification. Some 25 orders, 188 families and 177 different genera were recorded, with 170 unique species. The most common specimens included the Australian paralysis tick Ixodes holocyclus (708 specimens submitted), the bird mite Ornithonyssus bursa (506), bed bugs Cimex spp. (149), moth flies Clogmia spp. (135), head lice Pediculus capitis (105), pubic lice Pthirus pubis (91) and scabies Sarcoptes scabiei (57). In 1211 samples submitted, there was no evidence for any life stages of arthropods. For these common samples, data analysed included yearly and seasonal trends, female vs. male patient submissions and the age classes of the patients. Some species such as I. holocyclus, O. bursa, Cimex spp., Clogmia spp. and P. capitis demonstrated strong seasonal trends. In the case of the female vs. male patients, there were significant differences in submissions with O. bursa, P. capitis, P. pubis and with the samples containing no arthropod evidence. Of these, only with P. pubis did more males submit than females. Younger ages classes (<10 years) were more associated with I. holocyclus and P. capitis, older patients >70 years) with scabies, mature females (50–69 years) with samples containing no evidence of arthropods and middle‐aged adults (40–69) with the remainder of the common samples. Key diagnostic features are included for some of the more challenging arthropod species to distinguish and as well as case studies provided of situations involving unique or unusual infestations. The data provides useful information on the risks that arthropods of medical importance pose to the community and will refine educational programs.